Photosynthesis of some drought resistant groundnut cultivars - Ma, Nguyen Van; Cuong, Cao Ba (Academia Journal of Biology, 2014)
The groundnuts have not only a high economy value but also they are very useful in improving the soil. We carried out a study of the photosynthesis of three groundnut cultivars TQ6, V79 and L05 at different growth periods and the change in drought conditions. According to the results measured by the Ultra compact photosynthesis system LCi, the photosynthetic intensity of these groundnut cultivars is different at the stages of the young and overmature nuts. The cultivar TQ6 always has higher photosynthetic intensity than the cultivars V79 and L05 . The drought conditions have a great influence on the photosynthesis of the groundnut plants at the flowering stage. Also, the photosynthetic intensity of the higher drought resistant cultivars reduces at least in the drought conditions.